The Impact of Hedonistic Lifestyle, FOMO, and Financial Literacy on Personal Financial Management among Gen Z Students in Pontianak with Self-Control as a Moderating Variable - Dwi Desi Wulansari; Heni Safitri; Dedi Hariyanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of hedonistic lifestyle, Fear of Missing Out (FOMO), and financial literacy on personal financial management among Gen Z students in Pontianak, with self-control as a moderating variable. The method used is a quantitative approach with a descriptive associative research method and Moderated Regression Analysis (MRA) technique. Data collection was carried out using primary and secondary data. Primary data was obtained through an online questionnaire (Google Forms) measured using a Likert scale with 5 response levels, while secondary data was obtained through literature study and official documents. The population of the study consisted of 74,149 Gen Z students in Pontianak, with a sample of 150 respondents. Instrument testing was performed through validity and reliability tests using SPSS, followed by classical assumption tests (normality, linearity, and multicollinearity), as well as hypothesis testing using F and t-tests at a significance level of 0.05. The results show that all research instruments are valid and reliable. The classical assumption test indicates that the data is normally distributed, there is no multicollinearity, and the relationship between variables is linear. The results of MRA equation I show that the hedonistic lifestyle and FOMO do not have a partial effect on personal financial management, while financial literacy has a significant effect. The results of MRA equation II show that self-control moderates the effect of hedonistic lifestyle and financial literacy on personal financial management, but does not moderate the effect of FOMO. The F test shows that the hedonistic lifestyle, FOMO, and financial literacy simultaneously have a significant effect on personal financial management, and the presence of self-control strengthens the research model.